Social Media Marketing and Customized Customer Relationship Management: The Implication For Marketing Performance of Budget Hotel Industry - Setiadi, Roby (School of Business, IPB University (SB-IPB), 2023)
The purpose of this research is to build a customized customer relationship management (CRM) model in relation to the utilization of social media marketing for improving marketing performance of budget hotels in West Java, Indonesia. Specifically, this research aims to empirically examine the influence of the utilization of social media marketing and customer database management on customized CRM and marketing performance. A total of 115 respondents consisting of general managers and marketing managers of budget hotels in West Java was selected as sample by using simple random sampling technique. By employing Structural Equation Modeling (SEM), the findings have found that social media marketing equipped with customer database management significantly affects the customization of customer relationship management (CRM). Furthermore, customized CRM has a significant effect on marketing performance of budget hotels. The findings highlight that social media enables hotel businesses to interact with customers on a one-to-one basis, which allows for a more personalized customer experience. By analyzing customers' social media behavior and interests, hotel marketers can tailor their marketing efforts to suit each customer's needs and preferences. With better customer data, budget hotel businesses can create targeted marketing strategies that effectively meet their customers' needs thereby enhancing their overall customer relationship management and marketing performance. Keywords: budget hotel, customer relationship management, database management, marketing performance, social media marketing